2000
DOI: 10.1177/000992280003900505
|View full text |Cite
|
Sign up to set email alerts
|

Infant Sleep Position Practices 2 Years Into the “Back to Sleep” Campaign

Abstract: Since the 1992 American Academy of Pediatrics (AAP) recommendation to put babies to sleep in the nonprone position and the subsequent 1994 "Back to Sleep" campaign, the U.S. rate of sudden infant death syndrome (SIDS) has decreased more than 40%. This study reports sleep position practices in the greater Philadelphia area during 1996 and 1997. Four hundred and ten parents of infants 6 months of age or less answered a questionnaire by interview in Philadelphia clinics and private pediatric offices from December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 8 publications
1
23
0
4
Order By: Relevance
“…Phrases such as "cocooning," "rest assured," "protective," "security," and "endless bonding" imply that comfort is equivalent to safety. Comfort is cited frequently by parents and other caregivers as the primary reason for placing infants prone, 16,[28][29][30][31] and the implication of comfort displayed in these advertisements is likely to be a powerful influence. Unfortunately, many of these pictures portray unsafe sleep environments, such as bed-sharing with another child or sleeping on a soft surface.…”
Section: Discussionmentioning
confidence: 99%
“…Phrases such as "cocooning," "rest assured," "protective," "security," and "endless bonding" imply that comfort is equivalent to safety. Comfort is cited frequently by parents and other caregivers as the primary reason for placing infants prone, 16,[28][29][30][31] and the implication of comfort displayed in these advertisements is likely to be a powerful influence. Unfortunately, many of these pictures portray unsafe sleep environments, such as bed-sharing with another child or sleeping on a soft surface.…”
Section: Discussionmentioning
confidence: 99%
“…SIDS is a condition, like RDS, for which a specific innovation had a large beneficial impact on infant survival. Following the recommendation by the American Academy of Pediatrics (AAP) that infants not be put to sleep in a prone position and the ''back to sleep'' campaign (mounted nationwide in 1994) (Gibson et al 2000;Frohna 2001, 2002;Willinger et al 1998), the SIDS rate dropped by more than one-third among singleton births. Research demonstrates that babies put to sleep in the supine position were at significantly lower risk of death from SIDS (Li et al 2003;Ottolini et al 1999).…”
Section: Sidsmentioning
confidence: 99%
“…More than a quarter (28%) of the group I face-down group was African-American infants compared to only 12% of group II face-other cases ( Table 1, P = 0.004). This is perhaps not surprising given that studies have shown African-American mothers place their infants prone for sleep more often than whites or Asians [23][24][25].…”
Section: Discussionmentioning
confidence: 99%